Late Holocene wet/dry intervals from Fuegian steppe at Laguna Carmen, southern Argentina, based on a multiproxy record - Borromei, Ana Maria (2018)
Late Holocene environmental conditions are reconstructed from a sedimentary core (LCTF2) retrieved from Laguna Carmen (53° 40′ 60″S, 68° 18′ 0″W, 29 m a.s.l.) in the Fuegian steppe, northern Tierra del Fuego, southern Argentina. The multiproxy study utilizes pollen/spores, algae, ostracods, palynofacies, Total Organic Carbon (TOC), carbonate content, and lithology. Findings show that grass communities developed over the landscape from 4200 to 1400 cal yr BP. After that, the plant communities fluctuated between grasses to scrubland vegetation. Changes in the lake level as indicated by the halophytes, algal content and ostracod associations, revealed alternation of wet and dry intervals. The palynofacies indicate environments close to the terrestrial source with a great input of terrigenous organic matter into the lake in agreement with the sedimentary environment. By comparison with other sites from Tierra del Fuego and southwestern Patagonia, the record of wind-carried Nothofagus pollen is consistent with variations in the Andean forest communities as a consequence of shifts in the latitudinal position and/or strength of the westerlies. The short-term wet/dry intervals seem to be associated with climate events of local occurrence. On the other hand, some wet intervals have been reported in lacustrine records from southern Patagonia. The last millennium showed high environmental variability. Humid conditions characterized the Medieval Climate Anomaly (MCA) event, while dryness conditions were related to the Little Ice Age (LIA) event. In particular this latter interval has been related to a northward migration of the westerlies from their present day focus.